IMPLEMENTASI PEMBINAAN WILAYAH SERTA PENATAAN GEOGRAFIS TERHADAP PULAU-PULAU KECIL DI KALIMANTAN TIMUR - Drs. H. Syachruddin (Pusjar SKPP Lembaga Administrasi Negara, 2005)
The north side of East Kalimantan Province is characterized by harsh bordering areas, both land and sea. There are 386 islands in East Kalimantan territory; and 138 of those are unanimous. Such condition requires suitable policy to manage and optimize natural resources as well as to accelerate socio economic development and people’s prosperity. It also aims at protecting environmental quality and preventing from alien’s threat and intervention. This paper elucidates the implementation of East Kalimantan Provincial Government’s territorial policy based on the strategic study (SWOT Analysis). It also explicates the principles and procedures of giving names to unanimous islands.